Explanation:
35x-7(4x+5)=(4x+22) -3(3x+11)
All terms are shifted to the left:
35x-7(4x+5)-((4x+22)-3(3x+11))=0
We add numerous parentheses.
35x-28x-((4x+22)-3(3x+11))
-35=0
Terms are calculated as follows: -((4x+22)-3(3x+11)), resulting in:
(4x+22)-3(3x+11)
We add numerous parentheses.
(4x+22)-9x-33
We eliminate parenthesis.
4x-9x+22-33
All the numbers and variables are added together.
-5x-11
Returning to the equation
-(-5x-11)
All the numbers and variables are added together.
7x-(-5x-11)-35=0
We eliminate parenthesis.
7x+5x+11-35=0
All the numbers and variables are added together.
12x-24=0
We shift every term that contains x to the left and every other term to the right.
12x=24
x=24/12
x=2